2020
DOI: 10.1017/s0025315420000016
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities and bioactive compounds of the ethyl acetate extract of the sea cucumberHolothuria forskalifrom Tunisian coasts

Abstract: Previous scientific studies have listed chemical compounds from sea cucumber species. The ability to produce bioactive metabolites derives from their response to various ecological stresses and avoidance of predation. In view of this, the present work aimed to evaluate the antibacterial activity and quantitatively assess the active components of different organs of the sea cucumber Holothuria foskali collected from the north-east of Tunisia. The antibacterial activity of ethyl acetate extracts was tested again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Sea cucumber phenolics also showed antibacterial activities against various bacteria. For instance, Telahigue et al [ 29 ] prepared ethyl acetate extracts from Holothuria forskali and tested them against Bacillus cereus , Bacillus subtilis , Pseudomonas aeruginosa , and Escherichia coli . It was found that ethyl acetate extracts are a good source of phenolic acids, which had the potential to inhibit E. coli and B. subtilis .…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sea cucumber phenolics also showed antibacterial activities against various bacteria. For instance, Telahigue et al [ 29 ] prepared ethyl acetate extracts from Holothuria forskali and tested them against Bacillus cereus , Bacillus subtilis , Pseudomonas aeruginosa , and Escherichia coli . It was found that ethyl acetate extracts are a good source of phenolic acids, which had the potential to inhibit E. coli and B. subtilis .…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…For instance, high-performance liquid chromatography coupled with a mass spectroscopy (HPLC-MS) was used to identify the phenolic compounds of Holothuria forskali extracts, which were mostly phenolic acids such as quinic, gallic, rosmarinic, and salvianolic acids. The same study reported that quinic acid was abundant in different body parts, including the digestive tract, muscle, body wall, gonad, and respiratory tree, whereas only gallic acid and caffeoylquinic acid were present in the gonads of this sea cucumber [ 29 ]. Moreover, the body wall of Holothuria atra was an excellent source of chlorogenic acid (up to 92 wt%), and it also contained pyrogallol, coumaric acid, rutin, and catechin [ 30 ].…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…14 The presence of vanillic, gallic, p-coumaric, and caffeic acids has previously been documented in different species of sea cucumber (H. tubulosa and Holothuria forskali). 47,48 Syringic acid [M − H] − at m/z 197 showed MS 2 fragmentation ions at m/z 109, 123, 153, 163, and 179, where 153 corresponded to the loss of carboxyl group. 49 Sinapic acid was discovered with an observed [M − H] − m/z at 223, where the MS 2 spectrum was 175, 179 (loss of carboxyl moiety), and 208, matching the characteristics of sinapic acid.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, Alper and Günes [ 43 ] identified epicatechin, 2,5-dihydroxybenzoic acid, ellagic acid, gallic acid, chlorogenic acid, 3,4-dihydroxybenzoic acid, p -hydroxybenzoic acid, vanillic acid, caffeic acid, p -coumaric acid, ferulic acid, cinnamic acid, rutin, naringin, and quercetin from the dried body wall of Holothuria tubulosa , and the most abundant component was epicatechin (790.091 µg/g). Moreover, Telahigue et al [ 44 ] identified quinic acid, gallic acid, caffeic acid, syringic acid, trans-ferulic acid, o-coumaric acid, rosmarinic acid, and salvianolic acid from dried Holothuria forskali , and among them, quinic acid was abundant in the digestive tract, gonad, and respiratory tree. Additionally, phenolic compounds were identified and quantified from the Holothuria atra and Holothuria arenicola , and the major compounds were found to be chlorogenic acid (80.34–92.86%), pyrogallol, rutin, coumaric acid, and catechin [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%